Longitudinal Range of the Eastward‐Traveling Equatorial Plasma Bubble Inducing Ionospheric Scintillation - P. Abadi; Y. Otsuka; S. Saito; M. Yamamoto; S. Perwitasari; I. N. Muafiry; A. Y. Putra; A. Faturahman (Space Weather)
Abstract Equatorial Plasma Bubbles (EPBs) can generate ionospheric scintillation at GHz frequencies used in the Global Navigation Satellite System (GNSS). Emerging at any longitude following sunset and typically moving eastward, monitoring the EPBs is essential for space weather services. Using three GNSS receivers positioned at the same latitude (∼0°N) but separated in longitudes (∼9°, ∼16°, and ∼25°) and the 47 MHz Equatorial Atmosphere Radar (EAR) in Indonesia, our study delineates the zonal extent of eastward‐traveling post‐sunset EPB inducing ionospheric GNSS scintillation. Typically, the scintillation occurrences detected by a ground receiver concentrate between 19 and 01 local time (LT), with a peak incidence observed at 21 LT. Furthermore, an experiment combining EAR observations with GNSS receiver data allowed for the determination of the linear change in the speed of eastward‐traveling EPB inducing scintillation during this time period. Interestingly, the longitudinal range of eastward‐traveling EPBs increased with higher solar flux (F10.7) levels. Our findings suggest that EPB can induce scintillation up to a longitudinal distance of approximately 25° from the onset location at sunset to the eastern midnight region, particularly in F10.7 ranging from 90 to 150 solar flux units. Moreover, experiments using longitudinally separated GNSS receivers indicated that scintillations during 19–01 LT originate from post‐sunset EPBs within a longitudinal range extending 25° to the west. In conclusion, our research provides valuable insight into the ability of eastward‐traveling EPB to induce GNSS scintillation within a longitudinal range of 25°, thereby enhancing EPB and scintillation monitoring and prediction in regional space weather services.